Consumption of Energy and AB Mix Nutrition in A Controlled Verticulture Hydroponic Applications of Curly Red and Green Lettuce - Hilda Agustina; Dika Tri Angraini; Veby Angela Putri; Endo Argo Kuncoro; Tri Tunggal; Fidel Harmanda (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
The green lettuce and Curly red lettuce have a high potential to be developed as commercial crops on limited land with verticulture cultivation system. The use of this cultivation system must be supported by adequate nutrients and water in addition to optimal environmental conditions. By using the vertical hydroponic plant cultivation method will increase the growth of Curly red and green lettuce plants. The method used is an experimental method and the data is processed using polynomial analysis method and descriptive method. The observation parameters in this study consisted of main parameters (flow rate, power requirement, energy requirement, and water pressure calculation). In addition, supporting parameters were evaluated including plant height, leaf count, fresh weight of plants, plant productivity, and harvest yield. Data were analyzed using descriptive and regression methods. The power requirement used from the initial stage of transplanting to harvest is 640.8 W. The total energy requirement used from the initial planting process to the harvest process is 2563.2 Wh. The average AB mix requirement of each stage of plant is 972.0 ppm; 1231.9 ppm; 1158.1 ppm; 1092.4 ppm. Flow rate is directly proportional to temperature; if the temperature increases, the flow rate for nutrients will increase, and if the temperature decreases, the flow rate will decrease for the fertigation system. Keywords: Energy, Hydroponic, Lettuce, Nutrition, Verticulture cultivation.